Dipeptidyl-aminopeptidase IV (CD26) in clinical diagnosis of cutaneous T cell lymphomas - Sokołowska-Wojdyło, Małgorzata; Maciejewska-Radomska, Agata; Barańska-Rybak, Wioletta; Lewandowski, Andrzej; Cegielska, Agnieszka; Roszkiewicz, Jadwiga (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Dipeptidyl-aminopeptidase IV, also known as CD26 antigen, plays a pivotal role in the pathogenesis of cutaneous T-cell lymphomas (CTCL). Nowadays it is believed that the loss of T-cell CD26 expression is a feature of circulating Sezary cells in peripheral blood. Objective. Evaluation of the loss of T-cell CD26 expression as a diagnostic and prognostic marker in patients with CTCL and erythrodermias caused by other inflammatory dermatoses. Material and methods. T-cell immunophenotyping by flow cytometry in 71 patients with CTCL, including Sezary syndrome, as well as with inflammatory skin diseases. Results. High levels of CD4+/CD7–/CD26– cells and concomitant low T4:T8 ratio were seen in patients with Sezary syndrome and highly advanced stages of CTCL. Conclusions. The loss of CD26 expression evaluated by flow cytometric immunophenotyping seems to be a useful method in dermatological practice for differential diagnosis of cutaneous T-cell lymphomas, especially Sezary syndrome. Probably the loss of T-cell CD26 antigen expression and high levels of Lutzner cells in peripheral blood in patients with inflammatory dermatoses may be a risk factor of CTCL development in future. It requires however further clinical observations.